Analytical Hierarchy Process (AHP) Supplier Selection Analysis on MSME Banana Chocolate Ajo Sikumbang in Pekanbaru City - Novrianti, Dian Puspita; Roidelindho, Kiki (Program Pascasarjana, Universitas Riau, 2022)
This study aims to select the best supplier by using AHP (Analitycal Hierarchy Process). The research method used is descriptive quantitative with criteria consisting of quantity, quality, cost, and delivery. The object of this research is UMKM in the food sector, known as Pisang Chocolate Ajo Sikumbang, which is located in the Panam area of Pekanbaru City. The data analysis for this research was conducted by comparing three suppliers of bananas, namely suppliers in Panam Market, Kualu Market, and Arengka Market. From the results of data analysis, it was found that the criteria for the quantity of bananas from suppliers became the most important factor for the Ajo Sikumbang Chocolate Banana business, with a value of 0.373, or 37%. Meanwhile, for alternative considerations, the performance of the three suppliers was obtained and the highest score was achieved by suppliers in the Panam Market with a value of 7,534.